Deep transcriptome profiling of clinical Klebsiella pneumoniae isolates reveals strain and sequence type‐specific adaptation. (10th September 2015) - Bruchmann, Sebastian; Muthukumarasamy, Uthayakumar; Pohl, Sarah; Preusse, Matthias; Bielecka, Agata; Nicolai, Tanja; Hamann, Isabell; Hillert, Roger; Kola, Axel; Gastmeier, Petra; Eckweiler, Denitsa; Häussler, Susanne
Summary: Health‐care‐associated infections by multi‐drug‐resistant bacteria constitute one of the greatest challenges to modern medicine. Bacterial pathogens devise various mechanisms to withstand the activity of a wide range of antimicrobial compounds, among which the acquisition of carbapenemases is one of the most concerning. In K lebsiella pneumoniae, the dissemination of the K. pneumoniae carbapenemase is tightly connected to the global spread of certain clonal lineages. Although antibiotic resistance is a key driver for the global distribution of epidemic high‐risk clones, there seem to be other adaptive traits that may explain their success. Here, we exploited the power of deep transcriptome profiling (RNA‐seq) to shed light on the transcriptomic landscape of 37 clinical K . pneumoniae isolates of diverse phylogenetic origins. We identified a large set of 3346 genes which was expressed in all isolates. While the core‐transcriptome profiles varied substantially between groups of different sequence types, they were more homogenous among isolates of the same sequence type. We furthermore linked the detailed information on differentially expressed genes with the clinically relevant phenotypes of biofilm formation and bacterial virulence. This allowed for the identification of a diminished expression of biofilm‐specific genes within the low biofilm producing ST258 isolates as a sequence type‐specific trait.